(untitled) (Web of Teachers: Inderscience Research, 2025)
This article provides an in-depth analysis of the extralinguistic factors of a lawyer’s speech in court proceedings - that is, the communicative and psychological impact of non-linguistic means (facial expressions, intonation, pauses, body language, gestures). In the context of investigation and trial, these factors are studied as a means of correctly interpreting speech, assessing the reliability of witness testimony, and inducing the necessary psychological impact on the audience. Based on the experience of the Uzbek judicial system and examples of international judicial practice, precautions in assessing extralinguistic signs, intercultural differences, and the risks of misinterpretation are analyzed on a scientific basis. Also, the role of perseveration in investigative interrogations, evaluative questions, and rhetorical devices in the orator’s speech are covered on the basis of examples. The article also pays special attention to such elements as technical aspects of judicial oratory, voice culture, and speech pace.